2021
DOI: 10.1111/odi.13767
|View full text |Cite
|
Sign up to set email alerts
|

KLF7 is associated with poor prognosis and regulates migration and adhesion in tongue cancer

Abstract: Head and neck squamous cell carcinomas (HNSCCs) often originate in the oral cavity, where the tongue mucosa is the most frequently affected site. Tongue squamous cell carcinoma (TSCC) has tendencies of local invasion and lymph node metastasis. Patients with advanced TSCC (stage III-IV) are at a high risk of recurrence, with an overall survival rate < 65% (Argiris & Eng, 2003;Warnakulasuriya, 2009).The Krüppel-like factor (KLF) family of transcription factors regulates multiple essential cellular processes in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…Recently, the interrelationship between MAP7 and TLR4 was also showed in inflammatory response [23]. Moreover, MAP7 was found to be associated with cell migration and adhesion in tongue cancer [24]. In our study, the result confirmed that the protein expression of KLF7 was markedly enhanced after LPS treatment and reduced after si-Klf7 transfection.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, the interrelationship between MAP7 and TLR4 was also showed in inflammatory response [23]. Moreover, MAP7 was found to be associated with cell migration and adhesion in tongue cancer [24]. In our study, the result confirmed that the protein expression of KLF7 was markedly enhanced after LPS treatment and reduced after si-Klf7 transfection.…”
Section: Discussionsupporting
confidence: 82%
“…Total cellular protein was extracted with RIPA buffer, and immunoblotting analyses were performed as described previously 14 . The following antibodies were used: anti‐CDK4 (DF6102, Affinity, 1:1000 dilution) and anti‐glyceraldehyde 3‐phosphate dehydrogenase (E‐AB‐20072; Elabscience, 1:2000 dilution).…”
Section: Methodsmentioning
confidence: 99%
“…KLF2, KLF4 and KLF5 were reported to be essential to maintain the pluripotent state of embryonic stem cells (40). Importantly, high expression of KLF members associates with poor survival of patients with cancer (41)(42)(43). Similarly, poor outcome of breast cancer also associates with high mRNA level of KLF8 (Supplemental Figure 3), suggesting a potential role of KLF8 in the breast tumor development.…”
Section: Discussionmentioning
confidence: 95%